Memahami Hakikat Manusia Berdasarkan Teori Konseling Psikoanalisis - Talitha Hasnabila Firjatullah; Siti Dwi Yasinta; Inggit Widyanika; Bakhrudin All Habsy (STIKes Ibnu Sina Ajibarang, 2024)
Psychoanalysis is a theory developed by Sigmund Freud where it is said that past experiences affect a person in the present. This research uses a literature review approach by collecting information from credible and relevant sources related to the topic discussed. Data collection by tracing, reviewing, and understanding the sources of journal writing that has been made previously from the last ten years. The results of the study show an explanation of Sigmund's theory which divides the level of consciousness into three, namely id, ego, and superego, which are the three elements that result in inner drive and give birth to healthy and unhealthy behavior. Not only studying this, this theory also looks at the basis or background of the emergence of these behaviors and explains the development of human personality. This theory emphasizes components such as motivation, emotions, and other internal aspects. In addition, it also argues that the development of a person's personality occurs through psychological conflicts that generally occur during childhood or early childhood.